2020
DOI: 10.1016/j.sna.2019.111705
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity MEMS pressure sensor utilizing bipolar junction transistor with temperature compensation

Abstract: The paper presents MEMS pressure sensor chip utilizing novel electrical circuit with bipolar-junction transistor-based (BJT) differential amplifier with negative feedback loop (PDA-NFL). Pressure sensor chips with two circuits have been manufactured and tested: the first chip uses circuit with vertical n-p-n (V-NPN) BJTs and the secondcircuit with horizontal p-n-p (L-PNP) BJTs. The demonstrated approach allows for increase of pressure sensitivity while keeping the same chip size. It also can be used for chip s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 15 publications
2
28
0
1
Order By: Relevance
“…The main goal of this development is achieving very high pressure sensitivity. The early PDA-NFL chip research [19,[27][28][29] for the range of -60...+60 kPa showed that the optimized circuit based on n-p-n type BJT (V-NPN) allows for sensitivity increase by 1.54 times relative to the alternative circuit with horizontal p-n-p (L-PNP) BJT. The disadvantage of L-PNP BJT circuit is a parasitic current from emitter of BJT to substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of this development is achieving very high pressure sensitivity. The early PDA-NFL chip research [19,[27][28][29] for the range of -60...+60 kPa showed that the optimized circuit based on n-p-n type BJT (V-NPN) allows for sensitivity increase by 1.54 times relative to the alternative circuit with horizontal p-n-p (L-PNP) BJT. The disadvantage of L-PNP BJT circuit is a parasitic current from emitter of BJT to substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Topology of chip PDA-NFL has significant difference with Wheatstone bridge analogs, which have similar membrane with three RIs. Two PRs have to be placed in one of maximum MS regions as shown in Figure 2(b) and Figure 3 [22]. Metallization from a thin layer of aluminum (WAl = 0.8 μm), which is necessary for PRs and BJT connection into electrical circuit, is located more than 80 μm from the edge of thinned membrane part.…”
Section: Fabrication Processmentioning
confidence: 99%
“…The new electrical circuit with bipolarjunction transistor-based (BJT) piezosensitive differential amplifier with negative feedback loop (PDA-NFL) is applied. The efficiency of PDA-NFL circuit has already been successfully demonstrated for sensors of medium pressure range for 60 kPa [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The creation of temperature sensor as separate chip allows elements to be independent from each other regarding the choice of initial semiconductor material, combination of technological processes and, most importantly, methods of pressure and temperature measurement. Pressure sensor can operate on the piezoresistive effect, using single sensitive element [39], classical Wheatstone bridge electrical circuit [40][41][42][43][44][45] or new development utilizing piezosensitive differential amplifier with negative feedback loop (PDA-NFL) circuit [46][47][48][49][50][51], or any other effects [4,6,23,26,37]. An additional advantage of temperature sensor creating as a separate chip is no effect of residual mechanical stresses from applying pressure to pressure sensor membrane.…”
Section: Introductionmentioning
confidence: 99%